Size- and defect-controlled anti-oxidant enzyme mimetic and radical scavenging properties of cerium oxide nanoparticles. (31st October 2018) - Vinothkumar, G.; Arunkumar, P.; Mahesh, Arun; Dhayalan, Arunkumar; Suresh Babu, K.
Abstract : Improved enzymatic activity and concentration-dependent selective activation of peroxidase and oxidase activity of combustion-synthesized nanoceria. Abstract : Excess production of reactive oxygen species (ROS) such as hydroxyl (HO˙) and superoxide (O2 ˙ − ) radicals affects the metabolic processes and plays a major role in diseases like cancer. Defect-structured nanoceria is a potential material for mimicking various natural antioxidant enzymes. However, tuning the oxygen vacancy defects through a simple synthetic strategy still remains a challenge. Due to its multi-enzymatic nature, ceria exhibits both pro-oxidant and anti-oxidant properties simultaneously which is vaguely understood and seriously limits its scope in therapeutics. Herein, we report the preparation of nanoceria using a combustion method under various fuel (lean, stoichiometric and excess) conditions and its influence on size and oxygen defect concentration is correlated with the structural, toxic and antioxidant properties. The smaller size and higher number of oxygen vacancy (Ce 3+ sites) defects achieved under fuel lean conditions significantly improved the antioxidant and radical scavenging properties as evidenced by enzyme kinetics. At low concentration, ceria exhibits protective effects (eliminates HO˙ radicals and H2 O2 ) but at a higher concentration, it exhibits oxidase activity by generating O2 ˙ − radicals irrespective of the pH conditions. Our results clearly demonstrate the activation of selective enzyme mimetic properties by controlling the ceria concentration which is of the utmost importance in antioxidant therapeutic and diagnostic applications.